The Henley Smith Collection - Smith, Jonathan Bayard, 1742-1812.
Correspondence, documents, memorabilia, printed matter, and prints of the Bayard family; genealogical papers of the Bayard, Dandridge, Denison, Henley, and Smith families; and financial records (1874-1890) of the Washington National Monument Society. Includes papers concerning John Adams, John Quincy Adams, Samuel Adams, Joel Barlow, Peter Bayard, Henry Clay, Benjamin Franklin, John Hancock, Thomas Jefferson, Marquis de Lafayette, James Madison, James Monroe, John Morris, Thomas Paine, John Howard Payne, William Penn, William Peters, John Randolph, Joseph Reed, David Rittenhouse, Caesar Rodney, Benjamin Rush, Benjamin Thompson (Count Rumford), George Washington, William Wirt, and John Witherspoon.
Delegate to the U.S. Continental Congress and merchant of Philadelphia, Penn.
Collection material in English.
Keywords: Adams, John, -- 1735-1826.; Adams, John Quincy, -- 1767-1848.; Adams, Samuel, -- 1722-1803.; Barlow, Joel, -- 1754-1812.; Bayard, Peter; Clay, Henry, -- 1777-1852.; Franklin, Benjamin, -- 1706-1790.; Hancock, John, -- 1737-1793.; Jefferson, Thomas, -- 1743-1826.; Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, -- marquis de, -- 1757-1834.; Lear, Frances Henley, -- -1793.; Lear, Tobias, -- 1762-1816.; Madison, James, -- 1751-1836.; Monroe, James, -- 1758-1831.; Morris, John; Paine, Thomas, -- 1737-1809.; Payne, John Howard, -- 1791-1852.; Penn, William, -- 1644-1718.; Peters, William; Randolph, John, -- 1773-1833.; Reed, Joseph, -- 1741-1785.; Rittenhouse, David, -- 1732-1796.; Rodney, Caesar, -- 1728-1784.; Rush, Benjamin, -- 1746-1813.; Rumford, Benjamin, -- Graf von, -- 1753-1814.; Smith, Samuel Harrison, -- 1772-1845.; Washington, George, -- 1732-1799.; Wirt, William, -- 1772-1834.; Witherspoon, John, -- 1723-1794.; Baird family; Dandridge family; Dennison family; Henley family; Smith family; Washington National Monument Society; Washington (D.C.) -- Social life and customs; Delegates, U.S. Continental Congress -- Pennsylvania; Merchants